(untitled) (ModaPalavra e-periódico, 2014)
Nearly two decades ago a research methodology applied to the study of dress has been spread out and has, ever since, increasingly influenced the teaching of fashion history (more than dress history) and research projects in undergraduate courses in Brazil. The study based on observation and analysis of artifacts, derived from the English expression “object-based research", is an approach which had already been widely used by professionals in areas such as archeology, anthropology, conservation of cultural heritage and museology and which is commonly related to material culture, cultural heritage and memory. This essay proposes a reflection on the dissemination of research and teaching practices in Brazil aiming to historicize dress through object based research, which, I understand, has developed into visual analysis. Concepts and theoretical frameworks which have been disseminated accross the country, such as a methodologycal approach to use object-based-research proposed by Jules Prown (1982), will be reacessed in order to open up new venues for research procedures in this field.